Amazing Trigonometry_6

Geometry Level 2

If x = 1 cos θ 1 + cos θ x=\sqrt { \dfrac { 1-\cos { \theta } }{ 1+\cos { \theta } } } , then state 2 x 1 x 2 \dfrac { 2x }{ 1-{ x }^{ 2 } } in terms of θ \theta .


This problem is a part of this set .
cot θ \cot { \theta } tan θ \tan { \theta } cos θ \cos { \theta } sin θ \sin { \theta }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

x = 1 cos θ 1 + cos θ Let t = tan θ 2 = 1 1 t 2 1 + t 2 1 + 1 t 2 1 + t 2 cos θ = 1 t 2 1 + t 2 = 1 + t 2 1 + t 2 1 + t 2 + 1 t 2 = 2 t 2 2 = t = tan θ 2 \begin{aligned} x & = \sqrt{\frac {1-\cos \theta}{1+\cos \theta}} & \small \color{#3D99F6} \text{Let }t = \tan \frac \theta 2 \\ & = \sqrt{\frac {1-\frac {1-t^2}{1+t^2}}{1+\frac {1-t^2}{1+t^2}}} & \small \color{#3D99F6} \implies \cos \theta = \frac {1-t^2}{1+t^2} \\ & = \sqrt {\frac {1+t^2-1+t^2}{1+t^2+1-t^2}} \\ & = \sqrt {\frac {2t^2}{2}} = t = \tan \frac \theta 2 \end{aligned}

Therefore, 2 x 1 x 2 = 2 tan θ 2 1 tan 2 θ 2 = tan θ \dfrac {2x}{1-x^2} = \dfrac {2\tan \frac \theta 2}{1-\tan^2 \frac \theta 2} = \boxed{\tan \theta} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...